2014
DOI: 10.1016/j.cub.2014.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of YAP by Mechanical Strain through Jnk and Hippo Signaling

Abstract: Mechanical forces affect all the tissues of our bodies. Experiments conducted mainly on cultured cells have established that altering these forces influences cell behaviors, including migration, differentiation, apoptosis, and proliferation [1, 2]. The transcriptional coactivator YAP has been identified as a nuclear relay of mechanical signals, but the molecular mechanisms that lead to YAP activation were not identified [3]. YAP is the main transcriptional effector of the Hippo signaling pathway, a major growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
186
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 36 publications
6
186
2
4
Order By: Relevance
“…We plated cells sparsely on ECMs made of polyacrylamide substrates of defined stiffness with fibronectin coupled to their surface, and performed immunofluorescence and Western blot analysis of YAP localization and phosphorylation, and analysis of F-actin integrity. In agreement with previous reports (8,9), in MEFs grown on stiff substrates (50 kPa), cells were well spread and exhibited stress fibers and strong nuclear localization of YAP, whereas on soft substrates (0.5 kPa), cells were poorly spread and YAP was excluded from the nucleus (Fig. 4, A and B).…”
Section: Mechanosensation Of Stiff Ecm Promotes Nuclear Localization supporting
confidence: 80%
See 1 more Smart Citation
“…We plated cells sparsely on ECMs made of polyacrylamide substrates of defined stiffness with fibronectin coupled to their surface, and performed immunofluorescence and Western blot analysis of YAP localization and phosphorylation, and analysis of F-actin integrity. In agreement with previous reports (8,9), in MEFs grown on stiff substrates (50 kPa), cells were well spread and exhibited stress fibers and strong nuclear localization of YAP, whereas on soft substrates (0.5 kPa), cells were poorly spread and YAP was excluded from the nucleus (Fig. 4, A and B).…”
Section: Mechanosensation Of Stiff Ecm Promotes Nuclear Localization supporting
confidence: 80%
“…In contact inhibited Drosophila epithelial tissue, myosin II contractility regulates the formation of the Wts kinase complex at AJs to suppress Hippo signaling, and in the absence of contractility this complex is disrupted and Hippo signaling is activated (15). Furthermore, in dense cultures in vitro, YAP nuclear localization is rescued by ECM stretching (9,10). Mechanoregulation of YAP in the absence of cell-cell contact has also been shown to be dependent on ECM stiffness sensation, myosin II motor activity, and cell spreading area (8,19).…”
mentioning
confidence: 88%
“…A recent study has shown that 6 h of oscillatory stretch of human mammary epithelial cells resulted in increased nuclear YAP levels, which was shown to correlate with cell proliferation 9. Another work has shown that culturing cells on stiff substrates resulted in a flat‐spread morphology with higher proliferation rates and an increase in nuclear YAP, as opposed to soft substrates, which resulted in a rounded cell shape, decreased proliferation rates, and more cytoplasmic YAP 27.…”
Section: Discussionmentioning
confidence: 99%
“…YAP can be localized in the cytoplasm or translocated to the nucleus, where it associates with TEAD transcription factors 7. Previous studies have shown that various forms of mechanical stimulation, such as substrate stiffness, strain, and shear stress, affected YAP localization by actin fiber remodeling 6, 8, 9, 10. YAP was shown to be involved in the effect of shear stress on ECs and blood vessels,10 however its role in the effect of mechanical strain on vascularization is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation